EFEK PENAMBAHAN TEPUNG DAUN PEGAGAN (Centella asiatica) TERHADAP PERFORMA PRODUKSI PUYUH - Yuli Arif Tribudi; Arina Nurfianti (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
Aim of this study was to know the effect of pegagan (Centella asiatica) on quail production performance. The material used in this study were 200 quail phase layer Coturnix-coturnix japonica strain. The method used was experimental design with completely randomized design (CRD) with 4 treatments and 5 replications. The treatment in this study was the feed control without the addition of pegagan meal (P0); feed control + 0,5% of pegagan meal  (P1); feed control + 1% pegagan meal (P2) and feed control + 1,5% pegagan meal (P3). The variables observed were feed intake (g/bird /day); Hen Day Production (%); feed conversion and egg weight (g/bird/day). The results showed of this research that pegagan meal not significant effect (P>0,01) on feed intake (g/bird/day), Hen day Production (%); feed conversion and egg wight (g/bird/day) in quail production performance. Feed intake, Hen day Production, feed conversion and egg wight best on P3 treatment and advised to do recommended pegagan meal in the feed of quail as much as 1,5% of the total feed. Keywords : Centella asiatica, Feed, Production Performance, Quail